STRATEGI INDUSTRI MANUFAKTUR DALAM MENINGKATKAN PERCEPATAN PERTUMBUHAN EKONOMI DI INDONESIA - Rafika Azwina; Pina Wardani; Fajar Sitanggang; Purnama Ramadani Silalahi (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
This study aims to determine the strategy of the manufacturing industry in increasing the acceleration of economic growth in Indonesia. The method used in this research is descriptive qualitative method. The data source used comes from secondary data through literature review or what is called literature study. industry in the manufacturing sector has contributed through a national scale economy of 20.27% in ASEAN. This can be seen through the development of manufacturing industry activities in Indonesia so that they are able to replace commodity-based and change to manufacture-based. The manufacturing industry strategy in increasing the acceleration of Indonesia's economic growth is carried out by implementing the industrial strategy 4.0 which is one of the plans for the establishment of the Indonesia Digital Industry Center 4.0 (PIDI 4.0)